Klasyfikacja pozycyjna w analizach dynamicznych - Strahl, Danuta (Positional Classification in Dynamic Analyses, 2008)
The article presents the proposal of the studied objects classification in a dynamic perspective. The procedure of objects division is divided into two stages. In the first stage the classification of objects is performed by means of positional statistics. The basic division criterion becomes the evaluation of attributes relations which describe the studied objects up to the median value. The procedure is repeated for each observation moment of values referring to the studied objects’ values. The second stage consists in the studied objects classification with reference to positions occupied by objects in particular moments of the study in the first stage of the classification. The classification criterion in the second stage becomes the frequency dominant of the studied objects’ classes, defined in the first stage of each moment of the study.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 27, s. 9-18